Amphiphilic nanostructure in choline carboxylate and amino acid ionic liquids and solutions. Issue 6 (28th January 2020) - Miao, Shurui; Atkin, Rob; Warr, Gregory G.
Abstract : The liquid structures of six choline carboxylate/amino acid ionic liquids (bio-ILs) and their mixtures with water and various n -alkanols have been investigated by small-angle X-ray scattering (SAXS). Abstract : The liquid structures of six choline carboxylate/amino acid ionic liquids (bio-ILs) and their mixtures with water and various n -alkanols have been investigated by small-angle X-ray scattering (SAXS). The ILs exhibit long-range amphiphilic nanostructure comprised of polar and apolar domains that can be controlled by choice of anion, and which is tolerant to water dilution. Mixtures with n -alkanols can lead to marked changes in domain size and ordering. Utilising the Teubner–Strey model, we find amphiphilicity factors in many of these mixtures are comparable to those observed in conventional microemulsions, and that cooperative assembly in bio-IL/alkanol mixtures can enhance amphiphilicity, with potential to improve performance in a range of applications.